HLA-DRB1*04 gene polymorphisms and expressions profiles of interleukin-18 and interleukin-18 binding protein following in vitro stimulation in human peripheral blood mononuclear cells of healthy individuals and patients with rheumatoid arthritis - Sivalingam, S.P. (2011)
10.1016/j.lfs.2007.02.020